Introduction to Spiniferites Mantell 1850 special issue. (20th December 2018) - Mertens, Kenneth Neil; Carbonell-Moore, Consuelo
Abstract: The first chapter of this special issue introduces the proceedings of two workshops concerning the cyst-based genus Spiniferites Mantell1850 . The historical background of the cyst-based genus Spiniferites, its closely related genera and the theca-based genus Gonyaulax Diesing1866 is presented here.